Analisis Sinonimitas Makna Nūr, Ḍiyā’, dan Sirāj dalam Al-Qur'an: Kajian Linguistik Semantik Berdasarkan Tafsir Al-Kasysyāf - ANWAR FAHMI (UIN Sunan Kalijaga Yogyakarta, 2024)
This article is motivated by the use of the words nūr, ḍiyā', and sirāj which are often translated as